Reinforced Concrete Finite Element Modeling based on the Discrete Crack Approach - Sri Tudjono; Han Ay Lie; Sholihin As’ad (Institute of Research and Community Outreach - Petra Christian University, 2016)
The behavior of reinforced concrete elements is complex due to the nature of the concrete that is weak in tension. Among these complex issues are the initial cracking and crack propagation of concrete, and the bond-slip phenomenon between the concrete and reinforcing steel. Laboratory tested specimens are not only costly, but are limited in number. Therefore a finite element analysis is favored in combination to experimental data. The finite element technique involving the cracks inserting is one of the approaches to study the behavior of reinforced concrete structures through numerical simulation. In finite element modeling, the cracks can be represented by either smeared or discrete crack. The discrete crack method has its potential to include strain discontinuity within the structure. A finite element model (FEM) including the concrete cracking and the bond-slip was developed to simulate the nonlinear response of reinforced concrete structures.